Gold Nanomaterial System That Enables Dual Photothermal and Chemotherapy for Breast Cancer - Lijun Wang; Binita Shrestha; Eric M. Brey; Liang Tang (MDPI AG, 2023)
This study involves the fabrication and characterization of a multifunctional therapeutic nanocomposite system, as well as an assessment of its in vitro efficacy for breast cancer treatment. The nanocomposite system combines gold nanorods (GNRs) and gold nanoclusters (GNCs) to enable a combination of photothermal therapy and doxorubicin-based chemotherapy. GNRs of various sizes but exhibiting similar absorbance spectra were synthesized and screened for photothermal efficiency. GNRs exhibiting the highest photothermal efficiency were selected for further experiments. GNCs were synthesized in bovine serum albumin (BSA) and integrated into citrate-capped GNRs using layer-by-layer assembly. Glutaraldehyde crosslinking with the lysine residues in BSA was employed to immobilize the GNCs onto the GNRs, forming a stable "soft gel-like" structure. This structure provided binding sites for doxorubicin through electrostatic interactions and enhanced the overall structural stability of the nanocomposite. Additionally, the presence of GNCs allowed the nanocomposite system to emit robust fluorescence in the range of ~520 nm to 700 nm for self-detection. Hyaluronic acid was functionalized on the exterior surface of the nanocomposite as a targeting moiety for CD44 to improve the cellular internalization and specificity for breast cancer cells. The developed nanocomposite system demonstrated good stability in vitro and exhibited a pH- and near-infrared-responsive drug release behavior. In vitro studies showed the efficient internalization of the nanocomposite system and reduced cellular viability following NIR irradiation in MDA-MB-231 breast cancer cells. Together, these results highlight the potential of this nanocomposite system for targeted breast cancer therapy.